Analisis Faktor- Faktor yang Mempengaruhi Motivasi Mahasiswa Profesi Ners Jurusan Keperawatan Unsoed Purwokerto - Upoyo, Arif Setyo; Sumarwati, Made (Jurnal Keperawatan Soedirman, 2011)
Profession Ners Program is continuing education program from scholar nursing. To finish that program need high motivation. Motivation influence result of studying. Objective. The aim of research identify factors that influence motivation nursing student in profession program. Method. There were 57 students as sample that taked ramdomized. Data was taked at the middle of profession program in 2009. Analyzed data used rank spearman. Result. The factor that have significant influence motivation are internal drives (p=0.000), task (p=0.035) and environment hospital (p=0.016). Conclusion. Time, method, academic mentor and clinical mentor have not given significant effect to motivation student. Recomendation. It’s recommended to increase internal drives and evaluate methoda, role of academic mentor and clinical mentor.